Eye movement disorders are an early manifestation of CACNA1A mutations in children. (27th January 2016) - Tantsis, Esther M; Gill, Deepak; Griffiths, Lyn; Gupta, Sachin; Lawson, John; Maksemous, Neven; Ouvrier, Robert; Riant, Florence; Smith, Robert; Troedson, Christopher; Webster, Richard; Menezes, Manoj P
Abstract : Aim: The alpha‐1 isoform of the calcium channel gene is expressed abundantly in neuronal tissue, especially within the cerebellum. Mutations in this gene may manifest with hemiplegic migraine, spinocerebellar ataxia type 6 (SCA6) and episodic ataxia type 2 (EA2) in adults. There are reports of children with CACAN1A mutations presenting with paroxysmal tonic upgaze, abnormal saccades and congenital nystagmus as well as severe forms of hemiplegic migraine. The aim of this study was to review the clinical presentation and subsequent course of all children with a CACNA1A mutation who presented to a tertiary children's hospital. Method: We reviewed retrospectively nine children with a proven CACNA1A mutation who presented to the Children's Hospital at Westmead between 2005–2015. The initial and subsequent clinical presentation, radiological features and molecular genetic profile of each child was reviewed. Results: Nine children presented to out institute over a 10 year period; six were female and three male. The median age of presentation was 1.2 years. Eye movement disorders were the presenting feature in eight children. Three of these children later presented with severe hemiplegic migraine episodes often requiring ICU care. Affected children also had developmental delay and developed classical hemiplegic migraine, episodic ataxia and seizures. Calcium channel blockers were used with some efficacy in preventing severe HM episodes. Interpretation: Eye movement disorders are an early manifestation of CACNA1A mutations in children. Improved recognition of the CACNA1A phenotype in childhood is important for early diagnosis, counselling and appropriate emergency management. There is some early evidence that calcium channel blockers may be an effective prophylactic agent for the severe hemiplegic migraine episodes. What this paper adds: Eye movement disorders are an early manifestation of CACNA1A mutations in children. Coma‐like episodes of hemiplegic migraine can be frequent in childhood and consideration needs to be given for appropriate acute and prophylactic management. This article is commented on by Bostan on pages539–540 of this issue.